Artificial Intelligence and Global Economic Inequality: Causes, Solutions, and Impacts - Sukmatica Slamet; Andi Batary Citta; Widiastuti (IECON: International Economics and Business Conference, 2024)
This study analyzes the relationship between the adoption of artificial intelligence (AI) and economic inequality, exploring policy solutions to mitigate AI's negative impact on inequality. A literature review approach was used, examining relevant studies, reports, and articles on AI’s effects on economic inequality. The findings indicate that AI can exacerbate global economic inequality through two primary mechanisms. First, AI-driven automation replaces low-skilled jobs, leading to higher unemployment among low-skilled workers. Second, reliance on advanced technology is concentrated in countries or groups with sufficient resources, leaving others behind. However, AI also presents opportunities to reduce inequality, especially if applied to sectors like agriculture and education in developing countries, which can foster economic growth. With appropriate policies, AI could drive economic progress while addressing socio-economic inequality. These policies would ensure that AI's benefits are widely accessible, promoting inclusive development rather than deepening disparities. Ultimately, AI has the potential to either widen or narrow economic gaps, depending on how it is integrated into society, underscoring the need for targeted strategies to harness its positive impact.